FORMULASI LOTION ANTIOKSIDAN EKSTRAK KULIT PISANG KEPOK (Musa balbsiana colla) MENGGUNAKAN EMULGATOR TWEEN 80 DAN SPAN 80 - Olii, Audia Triani; Musyid, Mumtihanah; Nurfitriani, Besse (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Kepok banana peels contain flavonoid compounds which can be used as antioxidants. Lotion is a type of cosmetic in the emollient (softener) category which has a higher air content. Its functions include maintaining skin moisture, cleaning, preventing moisture loss or retaining active ingredients on the skin. The use of an appropriate combination of emulsifiers between Tween 80 and Span 80 in lotion preparations can form an optimal oil-in-water type emulsion. The aim of this research is to optimize the formulation of kepok banana peel extract lotion (Musa balbisiana colla) with Tween 80 and Span 80 as emulsifiers. The research results showed that the lotion formula was optimized to produce a formula using Tween 80 : Span 80 of 9% : 1%, which had a pH value of 6.4467, viscosity of 12860 cPs, adhesive power of 5.66 seconds, spreadability of 6.4 cm/ seconds, and the antioxidant activity test was 79.9249. Meanwhile, the results of stability testing of the optimum lotion formula showed good stability in homogeneity, pH, spreadability and adhesion tests. However, the viscosity test was unstable.